ISOLASI DAN IDENTIFIKASI JAMUR KAYU DARI HUTAN PENDIDIKAN DAN LATIHAN TABO-TABO KECAMATAN BUNGORO KABUPATEN PANGKEP - Astuti Arif; Musrizal Muin; Tutik Kuswinanti; Fitri Harfiani (PERENNIAL, 2007)
Wood deterioration were generally occured by the activities of biological agents. Fungal can attack wood and lignoselulosic substances and cause staining and decaying. Its damage levels were vary depending on the attacking fungal species. Eventhough it poses some disadvantages, actually fungy have potential benefits for human life such as nutrient, energy resources, medicine, etc. Fungy from Tabo-tabo educational forest were collected, isolated,and identified in this study. Identification was conducted throughout their macroscopic and microscopic characteristics. The result showed that the amount of fungal species were nineteen species, i.e: Aspergillus sp.,Poria subacida, Fomes sp., Lenzites sp., Hericium sp., Dacrymyces deliquescens, Ganoderma lucidum, Clitocybe sp., Trametes confragasa, Shizophyllum commune, Periconia sp., dan Helicosporium sp.,Clitocybe sp., Schizophyllum commune, dan Hygrophorus hypotejus,Ganoderma lucidum dan Coprinus atramentarius, Amanitopsis fulva dan Dacrymyces deliquescens, Collybia sp., Amanitopsis fulva, Hygrophorus hypotejus,Coprinus atramentarius, Monilia sitophilia, Gilmaniella sp. dan Conoplea sp. Key words: Wood fungy, deterioration, Tabo-tabo Educational Forest References